Inverse kinematic alignment accommodates native coronal knee alignment better in comparison to adjusted mechanical alignment and restricted kinematic alignment - Winnock de Grave, Philip; Luyckx, Thomas; Van Criekinge, Tamaya; Müller, Jacobus Hendrik; Ollivier, Britt; Van Eecke, Eduard; LiArno, Sally; Faizan, Ahmad; Claeys, Kurt (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2023)
Purpose The purpose was to determine the proportion of native non-arthritic knees that fit within the target zones of adjusted mechanical alignment (aMA), restricted kinematic alignment (rKA), and inverse kinematic alignment (iKA), and to estimate adjustments in native coronal alignment to bring outlier knees within the respective target zones. The hypothesis was that the target zone of iKA, compared to the target zones of aMA and rKA, accommodates a higher proportion of native non-arthritic knees. Methods The study used measurements obtained from a computed tomography (CT) scan database (SOMA, Stryker) of 972 healthy knees (Caucasian, 586; Asian, 386). Hip knee ankle (HKA) angle, medial proximal tibial angle (MPTA) and lateral distal femoral angle (LDFA) were used to estimate the proportions of knees within the patient-specific alignment target zones; and to estimate theoretical adjustments of MPTA, LDFA and soft tissue balance (HKA) to bring outlier knees within target zones. Theoretical adjustments to bring outlier knees within the alignment target zones of aMA, rKA and iKA were calculated by subtracting the native coronal alignment angles (MPTA native , LDFA native and HKA native ) from angles on the nearest target zone border (MPTA target , LDFA target and HKA target ). Results Patients were aged 59.8 ± 15.8 years with a BMI of 25.0 ± 4.4 kg/m 2 . The HKA angles were between 168° and 186°, MPTA between 78° and 98° and LDFA between 79° and 93°. Of the 972 knees, 81 (8%) were in the aMA target zone, 530 (55%) were in the rKA target zone, and 721 (74%) were in the iKA target zone. Adjustments of MPTA, LDFA and HKA angle to bring outlier knees within the target zones, were, respectively, 90, 91 and 28% for aMA, 45, 28 and 25% for rKA, and 25, 23 and 7% for iKA. Conclusions There is considerable variability in native knee coronal alignment that corresponds to different proportions of the restricted patient-specific alignment target zones for TKA. Although extension of the MPTA and LDFA target zones with rKA accommodate native knee alignment better than aMA, up to 25% would require adjustment of native HKA angle. By also extending the HKA angle target zone into varus, iKA accommodates a greater proportion (93%) of native limb alignment. Level of evidence IV.